Aplicação de dados multisensor (SAR e ETM+) no reconhecimento de padrões de uso e ocupação do solo em costas tropicais: Costa Amazônica, Amapá, Brasil - SANTOS, Valdenira Ferreira dos (2014)
Environmental studies require information on land use and land cover. This paper presents the applicability of multi-sensor satellite data (optical and radar) for land use and land cover on the Amapá coastal plain for mapping and recognition of natural and anthropogenic dynamics. This area is influenced by the Amazon River, by tides (tidal bore) and by the Intertropical Convergence Zone (ITCZ). Anthropogenic processes are associated with water buffalo ranching. The environmental information was acquired from previous data and field observation and was correlated with remote sensing data (JERS-1, RADARSAT-1, image from ETM+ sensor from Landsat 7 and DEM SRTM), digitally processed for multi-sensor, multi-scale and multi-date approach. Eight patterns of land use and land cover were identified (mangrove, "várzea" forest, arbustive vegetation area, freshwater marsh, anthropic field, intertidal plain, estuarine channel and lakes) as well with indication of natural and anthropogenic geomorphic features. The results from the evaluation of remote sensing data and the techniques applied demonstrated the potential of the remote sensing tool for studying environments in highly dynamic tropical coastal areas of difficult access. However, these tools may present some limitations once applied to application to the Amazon coast, which is a region under strong dynamic natural and anthropogenic processes.